Comparison sensitivity of 1% clotrimazole and 2% acetic acid to patient’s otomycosis isolates - Feby Valentin Ginting; Indri Adriztina; Yoan Carolina Panggabean; Yunilda Andriyani (Oto Rhino Laryngologica Indonesiana, 2026)
Background: Otomycosis is a challenge in the medical field, because it requires long-term treatment and follow-up and has a high recurrence rate. In the administration of otomycosis therapy, there are various problems, such as the occurrence of resistance, difficulty in drug application, and requires a long period of time for management. Therefore, choosing the right treatment regimen is very important, so as to reduce the level of resistance caused by the fungus that causes otomycosis. Purpose: To compare the sensitivity of 1% clotrimazole cream and 2% acetic acid solution to fungal isolates of otomycosis patients. Method: This study used true experimental design in vitro with post-test only control group design. Sampling was done by total sampling method during the August-November 20215. Eleven samples were obtained and tested on 3 treatment groups with repetition 3 times, so there was a total of 33 specimens studied. Result: The statistical calculations with the Kruskal-Wallis test from 11 samples tested, obtained a p value < 0.05 which indicated that there was a significant difference in the sensitivity of 1% clotrimazole cream and 2% acetic acid solution. Conclusion: The sensitivity of 1% clotrimazole cream and 2% acetic acid solution has a significant difference on fungal isolates of otomycosis patients